Embryological basilar apex disposition as a risk factor of basilar apex aneurysm. (December 2018) - Matsukawa, Hidetoshi; Kamiyama, Hiroyasu; Noda, Kosumo; Ota, Nakao; Takahashi, Osamu; Shonai, Takaharu; Tokuda, Sadahisa; Tanikawa, Rokuya
Highlights: Basilar apex (BA) aneurysm is one of the predictor of subarachnoid hemorrhage. BA is formed by the fusion of both caudal internal carotid divisions on the midline. Patients with BA aneurysm, other location aneurysms, and controls were compared. Symmetric cranial fusion BA type was associated with BA aneurysm. BA morphology may aid in the understanding of the pathogenesis of BA aneurysm. Abstract: The pathogenesis of basilar apex aneurysm (BAA) are still poorly understood. Embryologically, basilar apex anatomical disposition is formed by the fusion of both caudal internal carotid divisions on the midline. To compare basilar apex morphology by embryological classification among patients with BAAs, anterior circulation aneurysms (ACAs), and controls. Prospectively collected data of 47 consecutive patients with unruptured BAAs (42 females and five males), age- and gender-matched 47 patients with unruptured ACAs, and 47 controls without any aneurysms were analyzed. Based on embryology, basilar apex morphology was classified into symmetric cranial fusion (SCrF), symmetric caudal fusion, and asymmetric fusion type. Posterior communicating artery (Pcom) was classified into hypoplastic, adult, or fetal type. The asymmetrical Pcom was defined as bilaterally different type Pcom. The ACAs located at the anterior communicating artery (n = 18), paraclinoid portion (n = 12), middle cerebral artery (n = 8), anterior cerebral artery (n = 5), the top of internal carotid artery (n = 2), and anterior choroidal artery (n = 2). Compared with the ACA group and controls, smoking, asymmetrical Pcom (fetal and adult type), and SCrF type were more prevalent in patients with BAAs by residual analysis. The multinomial logistic regression comparative analysis demonstrated that SCrF type was associated with BAAs (vs. ACA group; odds ratio, 13; 95% confidence interval, 3.8–41 and vs. controls; odds ratio, 25; 95% confidence interval, 5.4–121). The assessment of basilar apex morphology may aid in the understanding of the pathogenesis of BAA and the prediction of BAA formation.